Biology, epidemiology and management of Pyrodinium red tides. - Hallegraeff, G.M. and MacLean, J.L. (ed.). (Manila, Philippines ICLARM, 1989)
ICLARM conference proceedings ; no. 21.
Keywords: Paralytic shellfish poisoning; Algae; Red tide